2020
DOI: 10.1007/s10916-020-01609-3
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Structured Reporting in Radiology: Implementation and Long-Term Evaluation in Improving the Communication of Critical Findings

Abstract: Structured reporting contributes to the completeness of radiology reports and improves quality. Both the content and the structure are essential for successful implementation of structured reporting. Contextual structured reporting is tailored to a specific scenario and can contain information retrieved from the context. Critical findings detected by imaging need urgent communication to the referring physician. According to guidelines, the occurrence of this communication should be documented in the radiology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…An example of the latter would be rectal cancer, where the exact anatomic location and extent of the tumor within the rectum directly affect the type of surgery. Such additions or modifications of structured reports, which can also be used to facilitate reporting of critical findings, are increasingly implemented in radiology under the term “contextual reporting,” with the aim to ensure report completeness from a clinical perspective [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…An example of the latter would be rectal cancer, where the exact anatomic location and extent of the tumor within the rectum directly affect the type of surgery. Such additions or modifications of structured reports, which can also be used to facilitate reporting of critical findings, are increasingly implemented in radiology under the term “contextual reporting,” with the aim to ensure report completeness from a clinical perspective [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…One potential idea was to create a structured reporting template, to ensure that communication between the radiologist and the referring clinician took place. These templates included three elements: (when) when the communication occurred, (how) by what method the communication took place, and (who) to whom the findings were communicated [ 22 ]. When tested in the clinical setting, the authors reported that communication of all three required items (when, how, who) was achieved in almost 100% of the reports containing the template, versus 5% of reports without the template.…”
Section: The Missing Link In the Chain Of Reporting: Let’s Close The ...mentioning
confidence: 99%